Implementasi Undang-Undang Tentang Administrasi Kependudukan Di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Aceh Timur - Sutejo, Denny; Kusmanto, Heri; Warjio, Warjio; Lubis, Anggreni Atmei (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
The purpose of this research is to analyze the implementation of Law Number 24 of 2013 concerning Population Administration in the Department of Population and Civil Registration of East Aceh Regency and to analyze the factors that influence it. This study used descriptive qualitative method. In general, the implementation of the policy of Law Number 24 of 2013 concerning Population Administration in the Office of Population and Civil Registration of East Aceh Regency has not been implemented properly. Several things that can be suggested include direct and continuous communication with the public, adding to the apparatus, completing facilities and making SOPs related to the implementation of the law.